Population pharmacokinetics and pharmacodynamics of edoxaban in pediatric patients - Peng Zou; Akhilesh Atluri; Peter Chang; Michael Goedecke; Tarek A. Leil (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Edoxaban is an orally active inhibitor of activated factor X (FXa). Population pharmacokinetic (PK) and pharmacodynamic (PD) analyses were performed to characterize the PK and PK–PD relationships of edoxaban in pediatric patients to identify the covariates that may contribute to inter‐subject variability in PK and PD of edoxaban in pediatric patients, and to compare the PK and PD data between pediatric and adult patients. The pediatric PK of edoxaban was best described by a two‐compartment model with transit compartments, first‐order oral absorption, and linear elimination. The estimated glomerular filtration rate (eGFR), body weight, and post‐menstrual age were the significant covariates explaining variability in edoxaban PK among pediatric patients. A function based on renal maturation was applied to edoxaban clearance. The clearance for a 70 kg patient with an eGFR of 110 mL/min/1.73 m2 was estimated to be 42.9 L/h (CV ~ 31.8%). PK simulation showed that exposures across five pediatric age groups were comparable to that in adult patients receiving 60 mg once daily dose. The PK–PD relationship for anti‐factor Xa was best fit with an Emax (8.65 IU/mL) model with an EC50 of 631 ng/mL. The PK–PD relationships for activated partial thromboplastin time and prothrombin time were best fit with linear models (slopes of 0.0467, and 0.0415 s mL/ng, respectively). In addition, due to the small number of efficacy and safety events, an exploratory analysis did not detect a correlation between efficacy events (recurrent venous thromboembolism) or safety events (clinically relevant bleeding) and edoxaban exposure.